The Effect Of Resistance Coil On The Performance Engine 4 Stroke Of Suzuki Satria Fu 150 - Abdurrahman, Reno; , Subroto,ST,MT (2016)
Abstract The purpose of this research were to knew the differences of power and torque output of four stroke motorcycle which given coil resistance variances between coil 1 with 8.63 kΩ, coil 2 with 7.16 kΩ, coil 3 with 3.12 kΩ. The research used experimental methods, given to a Suzuki Satria fu 150 motorcycle. Output data research analyzed by direct observation experiment output data then concluded and determinate output data research into table and graph. The experiment used dynamometer device to found the power and torque. The research result showed there were differences power and torque by three coil. The maximum power output obtained at coil 3 with 8.05 Hp, while the minimum power output obtained at coil 1 with 5.1 Hp. The maximum torque output obtained at coil 3 with 12.99 Nm, while the minimum torque output obtained at coil 1 with 4.8 Nm. Keywords : Coil resistance, torque, and power.